Numerical study of ejector as an expansion device in split-type air conditioner - Sumeru, K. (2013)
This paper presents a numerical approach for determining the motive nozzle and constant-area of an ejector as an expansion device, based on cooling capacity of the split-type air conditioner using R22 as working fluid. The use of an ejector as an expansion device in split-type air conditioner can enhance the coefficient of performance (COP) system. Typically, the split-type air conditioner may be installed on the geographical area with moderate or high outdoor air temperature using capillary tube. For this reason, the motive nozzle and constant-area diameters of the ejector must be designed according to these conditions. The diameters of the ejector are crucial in improving the COP. The results showed that the motive nozzle diameter is constant (1.14 mm) with variations of the condenser temperature, whereas the constant-area diameter decreases as the condenser temperature increases.